Disfunção do trato urinário inferior: impacto do tratamento e fatores de risco para o espessamento da parede vesical e cicatriz renal em crianças e adolescentes - Roberta Vasconcellos Menezes de Azevedo (2012)
This historical cohort of a 15 year follow-up aimed to evaluate the clinical, laboratory and imaging of children and adolescents with lower urinary tract dysfunction (LUTD), the impact of treatment and analyze the risk factors for thickening bladder wall and renal scarring. Data were collected from medical records of the patients and the clinical, laboratory and imaging were evaluated by univariate analysis and logistic regression. The study included 192 patients (123F, 69M), aged 0.1 to 16.8 years, enrolled in a university out-patient clinic divided into two groups: G1- with thickening of the bladder wall; G2-with no thickened bladder wall, analyzed at admission (T0) and at final follow-up (T1). Most patients were female (64.1%) and belong to a neurologic bladder dysfunction group (60.4%). The main symptoms of lower urinary tract were daytime urinary incontinence (82.3%), the non-monosymptomatic nocturnal enuresis (78.6%), fecal incontinence (54.2%) and constipation (47.9%). The bladder wall thickening was observed in 31.8%, the vesicoureteral reflux (VUR) in 33.1% and the presence of renal scarring in 15.6% of patients. Out of 61 patients with bladder wall thickening at admission, 55.7% maintained this condition, while in 44.3% there was a regression of the thickening in the final follow-up. However, of the 131 patients who had normal bladder thickening at admission, most (69.5%) remained with normal bladder and in 30.5% the bladder wall was thickened at the final follow up. The variables: male gender (p = 0.036), neurological group (p = 0.002) and presence of bladder diverticulum (p = 0.041) were risk factors for the development of thickened bladder wall in children and adolescents with LUTD. The bladder wall thickening (p = 0.033) and VUR (p = 0.0001) remained independent predictors for renal scarring on admission while the presence of VUR (p = 0.0001) and pelvic and / or renal calices dilatation (p = 0.001) were found to be independent predictors of renal scarring at final follow up. The treatment was uroterapy with behavioral and cognitive intervention, timed voiding, oral hydration, laxative diet, biofeedback, sacral nerve stimulation, bladder emptying maneuvers, institution of clean intermittent catheterization (CIC), anticholinergic therapy, rectal enema, treatment of febrile urinary tract infection (UTI) and, in refractory cases, surgical procedures such as incontinent and continent vesicostomy, bladder augmentation and conduit for performing antegrade colonic enema. There was a significant reduction of UTI (p = 0.0027), daytime urinary incontinence (p <0.001), the non-monosymptomatic nocturnal enuresis (p <0.001), fecal incontinence (p = 0.010) and of VUR (p = 0.01); however increased pielocalicinal dilatation (p = 0.04) and dilatation of ureter (p = 0.002) were observed. There was also a significant increase in the use of CIC (p=0.026) and anticholinergic therapy. This study showed that treatment of LUTD in children must be individualized, and requires constant monitoring of clinical, laboratory and imaging, to prevent the development of thickened bladder wall, RVU, dilatation of renal pelvis, calices and ureters, therefore minimizing the risk of kidney damage.